Narcissism and Performance on Behavioral Decision‐making Tasks. (13th September 2015) - Brunell, Amy B.; Buelow, Melissa T.
Abstract: Three studies examined narcissism and behavioral decision making. Decision‐making tasks included the Iowa Gambling Task (IGT; Studies 1–3), Balloon Analogue Risk Task (Studies 1–3), Columbia Card Task (CCT; Studies 2 and 3), and Game of Dice Task (Study 3). To tease apart the contributions of grandiose narcissism (i.e., narcissism found in the general population), pathological narcissism, and narcissistic traits (i.e., grandiosity, entitlement, and exploitativeness) in decision making, we assessed grandiose narcissism in Studies 1 ( n  = 380) and 2 ( n  = 244), pathological narcissism in Study 2, and the narcissistic traits in Study 3 ( n  = 312). Grandiose and pathological narcissism failed to predict decision making regardless of whether or not decision making included immediate feedback. In Study 3, the narcissistic trait of grandiosity (i.e., having an inflated sense of self‐importance) was associated with greater risk taking on the CCT‐hot (i.e., provided immediate feedback), and entitlement was associated with greater risk taking on the IGT. Measurement and applied implications are discussed. Copyright © 2015 John Wiley & Sons, Ltd.